Rationalism and the Future of Islamic Politics in Indonesia - NURUS SHALIHIN (Universitas Muhammadiyah Yogyakarta, 2013)
This paper aims to examine the Muslim rationality in legislative and executive election, and also tounderstand the reason why they choose national party, or Islamic party based on the alkali data oflegislative and executive election in West Sumatera from 2004-2009 periods. The paradigm of research isa rational choice theory. This paradigm helps to understand the political behavior of Muslim in WestSumatera in legislative and executive election of 2004-2009 period. Finally, the research finds out thatMuslim in West Sumatera always make a political choice rationale, and ignore the primordialconsideration to choose the party. This fact is crucial factor why the Islamic party was lost in WestSumatera, and other places in Indonesia.